2009
DOI: 10.1111/j.1365-2478.2009.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Operator‐oriented CRS interpolation

Abstract: A B S T R A C TIn common-reflection-surface imaging the reflection arrival time field is parameterized by operators that are of higher dimension or order than in conventional methods. Using the common-reflection-surface approach locally in the unmigrated prestack data domain opens a potential for trace regularization and interpolation. In most data interpolation methods based on local coherency estimation, a single operator is designed for a target sample and the output amplitude is defined as a weighted avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Another benefit of the CRS operator is the seismic data regularization (Hoecht et al . ; Xie and Gajewski ) by interpolating seismic traces to positions with missing or null traces. This benefit is also observed and extended to the pre‐stack data in the CO CRS method.…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit of the CRS operator is the seismic data regularization (Hoecht et al . ; Xie and Gajewski ) by interpolating seismic traces to positions with missing or null traces. This benefit is also observed and extended to the pre‐stack data in the CO CRS method.…”
Section: Introductionmentioning
confidence: 99%
“…These contributions are tested by coherence analysis for each ZO sample, and the set of attributes, which yield the highest coherency, is accepted as the optimum operator parameters to perform the actual stack (Höcht et al 2009). Figure 2c, shows the green CRS stack operator compared to the conventional CMP stack in Fig.…”
Section: Conflicting Dips Problem In the Crsmentioning
confidence: 99%
“…The same technique was applied by Höcht et al (2009) for the interpolation in the CS and CMP domain. Müller et al (2010) showed the potential of the CO-CRS method for regularization and S/N improvement of complete pre-stack datasets, as well as the superiority of the method with respect to the ZO-CRS-based data enhancement for data containing non-hyperbolic move-out.…”
Section: The Common-offset Crs Stackmentioning
confidence: 99%